Evaluating the quality of municipal services according to the financial budgets for years 2006-2016 Analytical research in Diwaniyah Governorate - جثير, سعدون حمود; حاكم, شيماء غانم (Journal of Economics and Administrative Sciences, 2020)
The research aims at determining the main reason for the deterioration of the services and determining the correct method of distributing the funds to the administrative and administrative units. The discrepancy between the size of the financial allocations and the municipal services was the main research problem. Therefore, the researcher identified the gaps in municipal services by the concerned departments and compared them with The percentage of funds obtained through the work of a checklist for each of the directorates concerned. The researcher studied the specific criteria for these services, which were approved by the Ministry of Construction, Housing, Municipalities, and Public Works, and compared them with the percentage of services provided to the citizens, which were measured from the data obtained from those departments and determining the gap in each type of municipal services. While the study community is the Directorate of Diwaniyah Municipality and water and sewage administrations in the governorate The researcher used the method of a comprehensive inventory of the research sample. The researcher relied on the data in these directorates for the purpose of collecting information and using the method of comparisons and extraction of gaps for analytical purposes, and the researcher reached a number of results, the most important of which is a large amount of money accompanied by mismanagement of this money, without services with a strategic dimension.